“Invasive” and “Non-invasive” Technologies in Neuroscience Communication - Gaillard, Maxence (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2017)
This paper analyzes a common distinction in neuroscience communication: the labels “invasive” and “non-invasive” attributed to brain-observation technologies. Because an implicit or explicit value judgment accompanies the term “non-invasive,” it has been used to promote technological progress, especially new brain-imaging techniques that have appeared in recent decades. This study’s material comes from interactions between some expert scientists and the political sphere. Expert reports on neuroscience from different advisory bodies in the French public sector have been collected and analyzed for use of the distinction between invasive and non-invasive. The paper shows that the meaning of these widely used labels varies according to the context, e.g., status of discourse, technologies compared, or stakeholders engaged in the discussion. The definition of what is understood as invasive or non-invasive becomes a strategic issue and can thus vary according to the methodologies favoured by experts participating in national advisory boards or councils.